17.6k views
23 votes
Can you anyone please help me?


Can you anyone please help me? ​-example-1
User Thushara
by
6.2k points

2 Answers

5 votes

Answer:

Well do you know the butterfly method

you multiply 2 by x+1 and 4 by x + 2

Explanation:

2(x+1) + 4(x+2) = 3(x-3) -2(x - 1)

2x + 2 + 4x + 8 = 3x - 9 - 2x + 2

2x + 4x +8 = 3x - 2x -9 +2

6x + 8 = x -7

6x - x = -7 -8

5x = -15

x = -15/5

x = -3

User Ringo
by
6.2k points
4 votes

Answer:

x = -
(29)/(7)

Explanation:


(x+1)/(4) +
(x+2)/(2) =
(x-3)/(2) -
(x-1)/(3)

Multiply through by 12 ( the LCM of 4, 2, 3 ) to clear the fractions

3(x + 1) + 6(x + 2) = 6(x - 3) - 4(x - 1) ← distribute parenthesis on both sides

3x + 3 + 6x + 12 = 6x - 18 - 4x + 4 , that is

9x + 15 = 2x - 14 ( subtract 2x from both sides )

7x + 15 = - 14 ( subtract 15 from both sides )

7x = - 29 ( divide both sides by 7 )

x = -
(29)/(7)

User Suba
by
5.1k points